Molecular-beacon-based screen for small molecule inhibitors of miRNA maturation - Bose, Debojit; Jayaraj, Gopal Gunanathan; Kumar, Santosh; Maiti, Souvik (ACS Chemical Biology, 2013)
miRNAs are small non-coding RNAs that regulate about 60% of mammalian genes by modulating their transcript levels. Network scale studies of miRNA-mediated regulatory circuits demonstrate the central importance of this class of small RNA in the maintenance of biological robustness. More recently, several reports have described the deregulation of numerous miRNA to be causally associated with many diseases, including cancer. These studies have highlighted the potential for development of therapeutic modalities against miRNA. Previous screening protocols, for small molecules targeting miRNA function, are either costly or technically too complex to be applied in a high-throughput manner in standard chemical laboratories. We describe a simple in vitro screening method using a DNA-based molecular beacon that overcomes the limitations associated with earlier screens. We used this method to identify inhibitors of miR-27a function from a library of 14 aminoglycosides as a pilot study. Inhibitory molecules identified were further scrutinized to identify the validity of screen. With this proof of concept we illustrate the utility of a scalable molecular-beacon-based screening strategy for miRNA inhibitors.

Morphological effects of G-quadruplex stabilization using a small molecule in zebrafish - Agarwal, Tani; Lalwani, Mukesh Kumar; Kumar, Santosh; Roy, Saumya; Chakraborty, Tushar Kanti; Sivasubbu, Sridhar; Maiti, Souvik (Biochemistry, 2014)
Zebrafish (Danio rerio) embryos are transparent and advantageous for studying early developmental changes due to ex utero development, making them an appropriate model for studying gene expression changes as a result of molecular targeting. Zebrafish embryos were injected with a previously reported G-quadruplex selective ligand, and the phenotypic changes were recorded. We report marked discrepancies in the development of intersegmental vessels. In silico analysis determined that the putative G-quadruplex motif occur in the upstream promoter region of the Cdh5 (N-cadherin) gene. A real-time polymerase chain reaction-based investigation indicated that in zebrafish, CDH-2 (ZN-cad) was significantly downregulated in the ligand-treated embryos. Biophysical characterization of the interaction of the ligand with the G-quadruplex motif found in this promoter yielded strong binding and stabilization of the G-quadruplex with this ligand. Hence, we report for the first time the phenotypic impact of G-quadruplex targeting with a ligand in a vertebrate organism. This study has unveiled not only G-quadruplex targeting in non-human animal species but also the potential that G-quadruplexes can provide a ready tool for understanding the phenotypic effects of targeting certain important genes involved in differentiation and developmental processes in a living eukaryotic organism.

Molecular modeling of non-canonical intramolecular RNA triple helix structures predicted from TRIPinRNA and their in vitro biophysical structure validation - Rakheja, Isha; Panda, Gayatri; Maiti, Souvik; Ray, Arjun (Journal of Physical Chemistry B, 2025)
RNA triple helices have traditionally been characterized by pyrimidine-type UA-U or CG-C triplets, with other base triplets considered to be destabilizing. However, the presence of non-canonical triplets in riboswitches and self-splicing introns suggests that triplexes containing longer stretches of such triplets may exist in the human genome too. Using molecular modeling, we investigated a chimeric triple helix derived from the FLRT2-AS1 lncRNA, confirming its stability over a 500 ns simulation. Biophysical analyses further support the formation of this triplex in vitro. Although these non-canonical structures exhibit less thermal stability compared to traditional UA-U triplets found in lncRNAs like metastasis associated lung adenocarcinoma transcript 1 and NEAT1, they may serve distinct biological functions, suggesting a dynamic and more temporal role in cellular processes. The triplex selected for this study is found in a human long non-coding RNA gene, paving the way for investigating the intriguing roles of these triple helices in cell biology.